(untitled) (Research, Society and Development, 2020)
The present study aims to report the functioning of a program developed in a unit of primary health care in the North of Brazil named “BBClin”, which promotes maternal and child care through the monitoring of women, during the gestational phase and in the puerperium, as well as the infant during its first thousand days of life, with comprehensive health care and encouraging the acquisition of healthy habits by the family, with the involvement of the entire Family Health Program team. It started in 2015 and continues to be developed to the present day. This is a qualitative and descriptive study, in the form of an experience report, about the history and implementation of the “BBClin” Program, being structured in four moments: Evolution of the “BBClin” program; Access to the program; Program functioning and functions by professional category. The “BBClin” program has established itself as a successful experience in several aspects, such as encouraging self-care for participating users, in addition to encouraging collaborative interprofessional work, in favor of comprehensive care, providing quality assistance to the population. The program is based on permanent education and counts with the participation of multiprofessional residents in family health and academics from different courses in the health area. In this sense, the example of the “BBClin” program may assist other health teams in the construction of similar work actions.